LEARNING ENGLISH FOR STUDENTS WITH SPECIAL NEEDS THROUGH SOCIAL CONSTRUCTIVISM PEDAGOGY-BASED JOYFUL LEARNING - Septi Gumiandari; Ilman Nafi'a (IAIN Syekh Nurjati Cirebon, 2021)
Students with special needs have different characteristics from students in general. Their different characteristics require more specific teaching services adjusted to their capacities and potentials. Their emotional, mental, intellectual, or social characteristics require special attention and treatment to strengthen their understanding of the learning materials. This article aims to explain the implementation of English language learning to students with special needs using joyful learning based on social constructivism pedagogy. This study employed a descriptive qualitative method and was conducted at SADA Ibu Inclusion School and Cirebon Pancaran Kasih Perjuangan Special Education. The findings of the research show that (1) the implementation of the joyful learning method encouraged students in English classes; (2) in combining joyful learning with a social constructivism pedagogy approach, the results hadÂ significant differences at the two schools. Joyful learning-based social constructivism pedagogy is more appropriately applied at SADA Ibu Inclusion School rather than in Cirebon Pancaran Kasih Perjuangan Special Education.